2021
DOI: 10.1007/s00170-021-07330-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different parameters on the tensile properties of printed Polylactic acid samples by FDM: experimental design tested with MDs simulation

Abstract: Fused Depositional Modeling (FDM) is one of the common methods for 3D printing of polymers, which is expanding in various industrial applications, scienti c researches, and engineering applications due to its ability to make complex parts. In this research, molecular dynamics (MDs) simulation has been used to predict the physical and mechanical properties. Then, the mechanical properties of the printed parts are obtained. The mechanical properties of 3D printed parts strongly depend on the correct selection of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 83 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…The selection of the infill pattern and density must be correlated with the stress and strain states for the future product. Both parameters are major factors of influence on the mechanical properties of 3D FFF-printed components [ 22 , 23 , 24 , 25 ]. The infill characteristics are to be set into the slicer software (addressed in the next step), but it is important to highlight that the infill selection is part of the design process of the component.…”
Section: From Pre-process Conditions To Mechanical Characterization O...mentioning
confidence: 99%
“…The selection of the infill pattern and density must be correlated with the stress and strain states for the future product. Both parameters are major factors of influence on the mechanical properties of 3D FFF-printed components [ 22 , 23 , 24 , 25 ]. The infill characteristics are to be set into the slicer software (addressed in the next step), but it is important to highlight that the infill selection is part of the design process of the component.…”
Section: From Pre-process Conditions To Mechanical Characterization O...mentioning
confidence: 99%
“…However, increases in strength have not been observed unanimously, as another study in ABS showed decrease in tensile strength when PS was increased from 10 to 50 mm/s (Abbott et al, 2018). A similar effect was seen in PLA over a range of 30-60 mm/s (Yu et al, 2019) and at 20 and 40 mm/s (Farazin and Mohammadimehr, 2021), where higher speeds decreased strength. It is possible that the discrepancy in results is because of the range of PSs being tested.…”
Section: Print Speedmentioning
confidence: 94%
“…Likewise, Abeykoon et al found the highest modulus for the linear pattern with respect to diamond, moroccanstar, catfill, sharkfill, hexagonal and Hilbert, due to the smaller spaces between the individual layers [9]. Considering the infill percentage, the highest Young's modulus has been reported for samples with a 100% infill percentage [1,4,9,15,16]. However, a lower infill percentage decrease the amount of material required and the printing time, which decreases the cost of printing [1,15].…”
Section: Introductionmentioning
confidence: 99%